Contraceptive use among Nigerian women with no fertility intention: interaction amid potential causative factors (2013)
High fertility (HF) remains a public health problem and the intention to reduce fertility is a global phenomenon. The health hazards and economic burden of HF on women are enormous. Contraception is widely known as a fertility reduction method. Achieving desirable MDGs and PoA of 1994ICPD will be an illusion if research on the relationship between fertility intention and contraceptive use is neglected. The study which focused on 2,257 women of childbearing age who do not have any intention to bear more children utilized the Nigeria Demographic Health Survey, 2008 dataset. Data was analysed using Chi-square, binary and multinomial logistic regression (=5.0%). The mean ages of the women and children ever born were 40.91±5.73 years and 6.28±2.62 respectively. The prevalence of Current Use of Any Contraceptive Method (CUACM) was 37.6%, with 12.4% and 25.2% currently using natural and modern family planning methods respectively. About 7.0% of women in the poorest wealth quintile are CUACM compared to 61.8% of those in the richest wealth quintile. The current use of modern contraceptive prevalence rate was strikingly higher among Yorubas (41.8%) than Hausas (3.6%). Multivariate analysis identified age, region, residence, education, ethnicity and family planning media exposure as significant predictors of CUACM. In addition, religion and decisions on how to spend family income were identified as predictors of current use of modern contraceptive methods (p<0.05). The use of contraceptives is not adequately practised in Nigeria. The identified predictors of contraceptive use in this study should be considered while designing strategies to improve the contraceptive prevalence rate in Nigeria.